Workplace Interventions Targeting Mental Health Literacy, Stigma, Help-Seeking, and Help-Offering in Male-Dominated Industries: A Systematic Review - Emilie Roche; Noel Richardson; Jack Sweeney; Shane O’Donnell (American Journal of Men's Health, 2024)
Mental ill-health and suicide represent a significant proportion of the burden of global disease among men. Connell’s relational theory of masculinities provides a useful framework to explore how mental health literacy, mental health stigma, and delayed help-seeking and help-offering behaviors are associated with mental ill-health among men, particularly within male-dominated industries. To address the high incidences of mental ill-health in male-dominated industries, several workplace interventions targeting these outcomes have been implemented. No review to date has examined the current state of evidence for these interventions or identified the behavior change techniques used. This review was restricted to empirical, quantitative research reporting on psychosocial interventions targeting mental health literacy, stigma, and help-seeking and help-offering behaviors in male-dominated industries. Quality appraisal was completed using the Effective Public Health Practice Project and a narrative synthesis was conducted. Twelve articles were included for review which reported on four distinct interventions. The methodological quality of two articles was strong, three moderate and seven weak. The strongest evidence of intervention effects related to mental health literacy and help-seeking intentions. There was less evidence relating to help-offering and help-seeking behaviors and mental health stigma. Sixteen behavior change techniques were identified across interventions that are discussed in relation to the wider men’s health literature. The evidence on psychosocial interventions in male-dominated industries is limited due to methodological and conceptual issues. Recommendations for future research include standardized reporting of intervention descriptions, the use of theory to guide intervention development, and utilizing validated and reliable outcome measures.